2019
DOI: 10.1891/2158-0782.10.3.104
|View full text |Cite
|
Sign up to set email alerts
|

From Policy to Practice: Women's Experiences of Breastfeeding-Friendly Worksites, Part 1

Abstract: IntroductionBreastfeeding-friendly worksites are associated with longer breastfeeding durations, yet currently there is a dearth of research exploring women's experiences of workplace-based wellness programs designed to support continued lactation.MethodUsing semi-structured interviews with a voluntary sample of participants from one rural New England town (N = 18), we examined women's experiences of returning to work at worksites with the Centers for Disease Control and Prevention (CDC)'s Worksite Health Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Fourteen studies were included and were reported across eighteen publications, of which nine out of fourteen studies were eligible to be included in the meta-analysis. Two studies (37,38) were ineligible for inclusion in the meta-analysis due to different study designs from other included studies, one study (39) was ineligible due to measuring breast-feeding rate in a different way from other included studies and two studies (40,41) were ineligible as they were qualitative studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen studies were included and were reported across eighteen publications, of which nine out of fourteen studies were eligible to be included in the meta-analysis. Two studies (37,38) were ineligible for inclusion in the meta-analysis due to different study designs from other included studies, one study (39) was ineligible due to measuring breast-feeding rate in a different way from other included studies and two studies (40,41) were ineligible as they were qualitative studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Nine publications (37,39,(45)(46)(47)(48)(49)(50)(51) reporting eight breast-feeding support programmes were cross-sectional studies, most of which participants had received an intervention. Three publications across two studies reported only qualitative results on women's breast-feeding experiences (40,41,52) . There were eight publications that represented multiple reports of four studies (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations